Differential prevalence of Adverse Childhood Experiences (ACEs) by gender and substance used in individuals with cannabis, cocaine, opioid, and tobacco use disorders. (4th March 2023) - Martin, Erin L.; Neelon, Brian; Brady, Kathleen T.; Guille, Constance; Baker, Nathaniel L.; Ramakrishnan, Viswanathan; Gray, Kevin M.; Saladin, Michael E.; McRae-Clark, Aimee L.
ABSTRACT: Background: Adverse childhood experiences (ACEs) show a graded association with the development of substance use disorders (SUDs) and engagement in risky substance use behaviors. Women are overrepresented among individuals with more severe childhood adversity (≥4 types of ACEs) and may be at particular risk for aberrant substance use. Objectives: To assess the prevalence of ACEs among men and women with cannabis, opioid, cocaine, and tobacco use disorders. Methods: Non-treatment-seeking individuals participating in clinical addiction research at a single site completed the ACE questionnaire and provided a detailed substance use history. Data were analyzed using proportional odds models and logistic regression. Results: Most participants (424/565; 75%) reported at least one ACE, and more than one-quarter (156/565; 27%) reported severe childhood adversity. Relative to men ( n  = 283), women ( n  = 282) reported more ACEs (OR = 1.49; p  = .01) and more experiences of emotional/physical abuse (OR = 1.52; p  = .02), sexual abuse (OR = 4.08; p  = .04), and neglect (OR = 2.30; p  < .01). Participants in the cocaine (OR = 1.87; n = .01) and opioid (OR = 2.21; p  = .01) use disorder, but not cannabis use disorder (OR = 1.46; p  = .08), studies reported more severe adversity relative to the tobacco group. Relative to tobacco users, emotional/physical abuse (OR = 1.92; p  = .02) and neglect (OR = 2.46; p  = .01) scores were higher in cocaine users and household dysfunction scores were higher in opioid users (OR = 2.67; p  = .01). Conclusion: The prevalence of ACEs differs with respect to both participant gender and primary substance used. Novel SUD treatment strategies that incorporate ACEs may be uniquely beneficial in specific subpopulations of people with SUDs.